“The Death of Saul”: One Text, Two Interpreters (Tchernichovsky and Zach) - Shoham, Reuven (MiKAN, 2012)
The narrative of King Saul, concluding with his death at Gilboa, is one of the archetypical “master narratives” that have shaped the Jewish national identity through the generations. Although it resurfaced in the historical play Reign of Saul by Yosef Ha-efrati of the Haskalah era, it was Berdycewski and mainly Tchernichovsky (in his ballads about Saul) of the “renaissance era” (shirat hatehiya), who transformed the story of the life and death of the first Israelite king into a personal and national story of heroism, a shaper of identity in the “Zionist master narrative”, and the antithesis of the narrative of the Jewish victim, who meets a martyr’s death. In the Hebrew poetry of the “statehood generation” (dor hamedina) – and specifically in the works of Amichai and, above all, Nathan Zach – this heroic narrative is put through a subversive test. Zach’s poems about Saul should be viewed as an attempt to subvert the biblical story and the heroic nationalization that Tchernichovsky imposed on it. Zach’s “Saul poems”, and especially his early opus “Death of Saul” (published in his inaugural collection, Early Poems – shirim rishonim), reveal the ideological crisis that Israeli society underwent after the War of Independence. His “Saul” is one of the first characters in modern Hebrew poetry who does not subscribe to the doctrine of “holy time”, which requires the individual to forsake his life on a mythical chessboard at times of national crisis that manifest themselves in crucial events such as wars. Zach refuses, or finds it difficult, to allow the first king to cooperate with the mythical Zionist time that Tchernichovsky, via the national master narratives that he wove into his poetry, did so much to shape in the first half of the twentieth century.